Mothers' Knowledge and Attitudes About Milk Eczema in Infants (0-24 Months) in Sianipar Village, Sub-District Balige Toba District - Jane Wilda Irmawati Sirait; Ricard F. Marpaung (Universitas Muhammadiyah Manado, 2024)
Milk eczema is a chronic, recurring skin inflammation accompanied by itching that is often experienced by infants. This milk eczema problem is actually not caused by breast milk (ASI) because from the results of a study conducted by Osborn (2007) it was found that babies who received breast milk intake for a longer time were less likely to experience milk eczema when compared to babies who had been given formula milk or solid food too early. The purpose of this study was to determine the knowledge and attitudes of mothers about milk eczema in infants (0-24 months) in Sianipar Sihail Hail Village, Balige District, Toba Regency in 2024. The design of this study was descriptive with a cross-sectional approach with a sample size of 38 people with a total sampling method. This study was conducted from October to November 2024. The instruments in this study were in the form of a questionnaire covering demographic data and a questionnaire on the knowledge and attitudes of mothers about milk eczema in infants (0-24 months). The results of the study showed that the majority of mothers had sufficient knowledge as many as 23 people (60.5%) and had a positive attitude 26 people (68.4%) about milk eczema. From this study, it is expected to be an input for every health worker in hospitals and private practices in improving the provision of information and understanding about milk eczema that occurs in infants, especially during immunization, considering that the incidence of milk eczema is still found today.